Teachers’ Familiarity, Readiness, and Anticipated Benefits and Barriers of Generative AI in Design and Technology Education - Tongchai, Apisit; Chuamklang, Sutthida; Rattanatippayaporn, Boonyawit; Suksai, Sayamchai; Metametha, Khajit; Pojananukij, Nusvadee (Journal of Social and Scientific Education, 2026)
The rapid advancement of generative artificial intelligence (GenAI) raises pressing questions about teacher readiness to integrate emerging technologies into classroom practice, particularly in Design and Technology education, where creativity and project-based learning are central. This study investigates teachers’ familiarity, readiness, and perceptions of GenAI following a targeted professional development workshop. A mixed-methods survey of 147 in-service teachers combined Likert-scale items with open-ended responses. Quantitative results indicated strong readiness and high perceived benefits, especially for fostering creativity, enhancing student engagement, and supporting project-based work. Correlation analysis showed that readiness was closely associated with perceived benefits, while barriers were less influential. Thematic analysis of open-ended responses highlighted four themes: pedagogical benefits, opportunities for professional growth, barriers to long-term adoption, and recommendations for sustained implementation. Overall, the findings reveal both enthusiasm and caution among teachers. While positive attitudes provide strong momentum for adoption, sustainable classroom integration will require institutional support, iterative and context-specific professional development, and clear policy guidance. This study contributes empirical insights into GenAI in education and offers practical implications for bridging teacher readiness with enduring classroom practice.